Information Extraction Using Text Mining by Keyword Ranking and Scoring - Gonnade, Priyanka; Bongade, Sarika; Mendhe, Tushar (International Journal of Computer Sciences and Engineering, 2014)
As the number of data is stored in a database, searching of a relevant data is the important issue in text mining. Though the today’s searching method provides us the relevant data but the numbers of results are too big to find the useful data. The needs of the user vary from time to time and they require different information at every instant of time. Keywords are useful for scanning large documents in a short time. Extracting keywords manually are very difficult and time consuming process. In this paper, we present the technique that are most likely able to satisfy the user’s needs and bring useful data in the top positions by extracting keywords from the data present in the database, scoring those keywords based on their occurrences and ranking the data based on keyword scores.